Barriers To Implementation of Industry 4.0 in Indonesia- Case of The Textile and Automotive Industries - Setiawan, Sigit; Poerbosisworo, Ishelina Rosaira (Jurnal Pekommas, 2022)
For several years, Industry 4.0 has become one of the buzzwords in the industrial world and has expanded to other areas. Industry 4.0 is an industrial revolution that is taking place today, where the internet and information networks use to create a new industrial revolution. Many benefits are expected to come from the application of industry 4.0 in a company/organization, primarily being able to open a highly customized market. Although there are various advantages to the application of industry 4.0 in a company/organization, the effort to implement it is not free from many problems. Likewise in Indonesia, although Industry 4.0 was launched directly by President Jokowi, and was followed by all sectors, the implementation effort still faces obstacles. Because of this, the question arises as to whether industry 4.0 is really needed in Indonesia or not. Therefore, it is worth seeing the effort to implement Industry 4.0 in Indonesia, especially in industries that should be able to implement Industry 4.0 easily. As in Germany, in Indonesia, the automotive manufacturing industry should be able to more easily apply the Industry 4.0 model. This paper discusses that added to the textile industry which should have similar properties. Discussion of the two industrial sectors at the same time has never been done in Indonesia. Meanwhile, one way to identify supporting and inhibiting factors is to use an analytical framework from Jan Stentof. Currently, the use of this analytical framework has not been widely used in Indonesia, particularly in the automotive and textile industries. By using an analytical framework from Jan Stentof to conduct an analysis, it was found that both the automotive and textile industries still have many obstacles to applying industry model 4.0. Many of the problems is related to communication both external and internal. It was also found from interviews, that at all levels there are often misconceptions between industry 3.0 and industry 4.0 models, so the application of industry 4.0 is even more difficult. With this study, we hope that government can adjust its policy to how to implement industry 4.0 in Indonesia. However, with only two sectors being researched, more sectors still need to draw a general conclusion.